Environmental Monitoring at and around the Matuail Landfill Site of Dhaka City using Remote Sensing - Sarker, Md Sayeduzzaman; Shoily, Umma Rafia; Chowdhury, Nokibul Alam; Ahmad, Rafsun; Ahmed, Afzal (Journal of Engineering Science, 2022)
Rapid urban population growth and flourishing incomes have increased waste production in Dhaka city. A part of daily produced Municipal Solid Waste (MSW) is disposed of at Matuail sanitary landfill located within Jatrabari Thana, Dhaka. This study has analyzed the environmental impacts at and around this landfill using remote sensing techniques. The objective of this research is to develop a means of environmental monitoring at the landfill site and its surroundings through the implementation of various time-series remote sensing indices e.g., Land Surface Temperature (LST), Normalized Difference Vegetation Index (NDVI), Soil Adjusted Vegetation Index (SAVI), and Modified Soil Adjusted Vegetation Index (MSAVI). LST is used to observe the Spatio-temporal pattern of temperature distribution. NDVI, SAVI, and MSAVI are the Bio-indicators and they are helpful to analyze the vegetation health condition at and around the landfill area. From the result of LST, it is observed that the average temperature of the Jatrabarithana has increased from 23.12℃ in 1993 to an optimum temperature of 35.20℃ in 2013, then it went down to 29.09℃ in 2018. The NDVI result for the study period shows that the percentages of ‘Bare Soil’ and ‘Structural Object’ have increased drastically from 10% to 41.20% and 13.30% to 31.52% respectively for these 25 years in Jatrabarithana. On the other hand, the percentages of ‘Shrub and Grassland’ and ‘Moderate Vegetation’ have decreased from 54.20% to 25.15% and 12.55% to 0% respectively. SAVI and MSAVI also show evidence of increasing the amount of bare soil and structural object and decreasing the amount of vegetation. Due to the waste stabilization process, and inappropriate management system at the Matuail landfill, along with urbanization, industrial activity, and deforestation, a harmful effect has been done to the surrounding environment. As an outcome, the temperature has risen rapidly and the amount of vegetation has declined to a significant extent. Journal of Engineering Science 12(3), 2021, 127-138